Prevalence and Predictors of Nonadherence to Diet and Physical Activity Recommendations among Type 2 Diabetes Patients in Southwest Ethiopia: A Cross-Sectional Study - Getandale Zeleke Negera; Dariowani Charles Epiphanio (International Journal of Endocrinology)
Background. Nonadherence to lifestyle modification recommendations is a major challenge in the management of diabetes mellitus. This study was conducted to measure the prevalence and predictors of nonadherence to diet and physical activity recommendations among type 2 diabetes patients (T2D). Methods. A cross-sectional study involving 322 type 2 diabetes patients was conducted from April 1 to June 30, 2019. Data were collected through face-to-face interviews using structured and pretested questionnaire. Data on sociodemographic, psychosocial, and clinical characteristics were collected. Descriptive analytical results were reported in text, tables, and figures. Logistic regression was conducted to identify predictors of nonadherence to diet and physical activity. Variables with p value ≤0.25 in bivariate logistic regression were considered as candidates for multivariable regression. Multivariate logistic regression was performed to identify independent predictors. Odds ratios and their 95% confidence intervals together with p value <0.05 were used to declare statistical significance. Result. The rate of nonadherence to physical activity and diet was 64.3% and 36%, respectively. Female gender (AOR: 2.6, 95% CI [1.52–4.56]), age > 60 years (AOR: 2.9, 95% CI [1.12–7.42]), being illiterate (AOR: 4.2, 95% CI [1.86–9.73]), diabetes duration of >5 years (AOR: 2.5, 95% CI [1.42–4.41]), and lack of social support (AOR: 2.4, 95% CI [1.42–4.35]) were independent predictors of nonadherence to physical activity recommendations. Factors associated with nonadherence to dietary recommendations were being male (AOR = 2.8, 95% CI: [1.35–5.65]), age > 60 years (AOR = 6.3, 95% CI: [2.21–18.17]), khat chewing (AOR = 8.0, 95% CI: [3.86–16.7]), lack of social support (AOR = 15.26, 95% CI = [7.45–32.8]), and doctor’s instructions or advice regarding diet (AOR = 8.9, 95% CI = [4.26–18.9]). Conclusion. The rate of nonadherence to diet and physical activity recommendations was high in the study area. Predictors of nonadherence to physical activity are female gender, age > 60 years, being illiterate, diabetes duration of >5 years, and lack of social support. Predictors of nonadherence to diet are being male, khat chewing, lack of social support, and doctor’s instructions or advice regarding diet.